Propuesta de manual de técnicas tradicionales de envueltos ecuatorianos - Ortega Jurado, Eugenia Karolina (2023)
The objective of this research project is to create a manual of traditional Ecuadorian wrapping techniques in order to preserve the valuable culinary knowledge that has been passed down through generations. The research is developed with a mixed approach based on the content analysis of 9 traditional Ecuadorian recipes. In addition, 6 interviews were conducted with traditional cooks and expert gourmets in order to document the empirical knowledge and to have an authentic and detailed vision of the culinary techniques. The results of the surveys and interviews revealed that 99% of the respondents have consumed salt wraps or sweets\; most of them are between 20 and 30 years old. In addition, 51% have consumed them rarely and it is evident that 62% have little knowledge about the correct preparation of the wraps. Ecuadorian chefs recognize that wraps do not need innovation because they have a unique presentation that should be present in gourmet restaurants\; it is important to promote their consumption and preparation. In conclusion, this research shows that Ecuadorian wraps are living symbols of the country's culinary identity and should be protected as a valuable intangible heritage. To guarantee their preservation, it is imperative to document the empirical knowledge of Ecuadorian cooks, who are the guardians of the ancestral knowledge that has been transmitted from generation to generation. This will have a positive impact on future gastronomes to guarantee the preservation of traditional culinary knowledge and encourage its elaboration to increase its consumption.